Relationship between corporate sustainability, corporate governance and financial performance - Asma Munir; Farman Ullah Khan; Muhammad Usman; Sobia Khuram (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
This study aims to investigate three crucial questions. First, whether the corporate governance and corporate sustainability leads to improved firm financial performance or not? Second, whether the sound corporate governance practices improve firm sustainable performance or not? Third, whether the corporate sustainability mediates the relationship between corporate governance and firm performance or not? We used the sample 425 firms listed on Australian Securities Exchange (ASX). Using structural equation modeling approach, we find that corporate governance is positively linkedto corporate sustainability performance, and corporate sustainability performance leads to improved financial performance. We also find that corporate sustainability performancemediates the link between corporate governance and financial performance. These findings are important for two aspects. The first is for firms' management, the regulators, policymakersin promoting corporate governance and corporate sustainability practices. Second, our study provides empirical support to current policy debate that investing in good governanceand better sustainability practicesis vital for long-term value creation.
Keywords: 330; sustainability performance; financial performance; corporate governance; ASX; Australia